Survey on Network and Device Aware QoS Approach for Mobile Streaming - Mohanakrishnan; Azath, M (International Journal of Computer Sciences and Engineering, 2015)
Cloud computing is an evolving technology designed to offer a variety of computing and storage services over the Internet. Cloud computing in multimedia is normally correlated with multimedia computing over grids, server-based computing, content delivery and peer to peer multimedia computing. Multimedia services offer a flexible, scalable, efficient data processing technique and it gives a solution for the user demands of best quality multimedia. Since the intelligent mobile phones, wireless networks and tablets have become more popular, network services for the users are no longer limited inside the home. Now public is in the use of mobile devices for watching the multimedia videos via streaming. Not all multimedia file formats are supported by all the mobile devices. Users always want to watch videos or files from everywhere at anytime, regardless of the changes in the network environments. To overcome the problem of limited available bandwidth for mobile streaming, surveyed the previous methods and introduced a network and device-aware QoS method that offers multimedia data which are appropriate for terminal unit. The wastage of bandwidth and terminal power could be avoided by choosing the appropriate transcoding format based on the bandwidth value. QoS method could endow with capable self adaptive multimedia streaming services based on the bandwidth environments.